Hubungan Kecerdasan Emosi terhadap Niat Mengatasi Kekerasan dalam Pacaran pada mahasiswa di Kota Semarang (Studi Kasus di Kecamatan Tembalang) - Mutia Tribuana Chansa; Syamsulhuda BM; Besar Tirto Husodo; Laksmono Widagdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Based on LRC-KJHAM, 94 cases of courtship violence were reported in Semarang City 2015. In Semarang the victims with a total of 51% were adolescents aged 18-25 years. The negative impact of courtship violence is very wide and varied as a has long-term psychological, sexual, physical, social.This study aims to analyze emotional intelligence relation to the overcomes of courtship violence among University students in Semarang. This descriptive analytic study usd quantitative approach. A crossectional design was used to sample 100 students through accidental sampling using Lemeshow Formula as the population could not be defined. Chi square was used to assess variabels that relate to the overcome of courtship violence behaviour. Most of the respondents are 22-23 years of age (86%) and the female category of respondents (63%). Respondents who have knowledge in the lack category (50%), the attitude of the respondents towards the excess category (55%), the subjective norm of peer respondents in the mid category (58%), the subjective norm of family respondent in the mid category (65%), the emotional intelligence respondents in the high category (55%), and the intention in the support category (81%).Chi Square test results find significant correlation between attitude, subjective norm of peers and emotional intelligence to quelling violence behaviour in college students courtship in Semarang. As for age, sex, knowledge, intention and subjective norms of family have no relation to quelling violence behaviour in college students courtship in Semarang.